PENGARUH RELEVANSI LABA AKUNTANSI TERHADAP RETURN SAHAM DENGAN RISIKO PERUSAHAAN DAN LEVERAGE SEBAGAI VARIABE PEMODERASI PADA PERUSAHAAN MANUFAKTUR DI BEI - HARYANTO, CAROLINA MARGARETH (Universitas Katolik Widya Mandala Surabaya, 2012)
Operations performance of company is measured based on the accounting earnings generated in a period. Accounting earnings is one reference for investors in making investment decisions. Relevance of accounting earnings shows the useful of accounting earnings by investors as a reference for investment decisions. The reaction of investors on the relevance of accounting earnings can be seen from the stock return. Some things affecting the relevance of accounting income on stock returns is the firm risk and leverage. This study aims to examine the effect of the relevance of accounting earnings to stock returns with firm risk and leverage as a moderator variable. The study design is quantitative. The object of research is manufacturing industries listed in Indonesia Stock Exchange in the year 2008-2010 as many as 50 companies selected by purposive sampling technique. Source data obtained from the Indonesia Stock Exchange. Techniques of data analysis was performed with multiple linear regression analysis. The results showed that the relevance of accounting earnings do not affect the return perusaaan and leverage as a moderator variable has no impact on the influence of the relevance of accounting earnings to stock returns. Meanwhile, firm risk is weakening the influence of relevance of accounting earnings to stock returns. This suggests that investors do not use only accounting earnings as the reference for investment decisions.